Birth weight percentiles by sex and gestational age for twins born in southern China - Miao, Huazhang (Sci Rep, 2019)
Mean birth weight of twins is known to be lower than that of singletons, however, southern China lacks a twin-specific birth weight reference. In this paper, we use data from the Birth Certificate System in southern China, collected between January 1(st) 2014 and December 31(st) 2017 and including 161,076 twins, to calculate sex- and gestational week-specific birth weight percentiles (the 3(rd), 10(th), 25(th), 50(th), 75(th), 90(th), and 97(th)). We applied generalized additive models for location, scale and shape (GAMLSS) when calculating the birth weight percentiles, and calculated percentiles for monochorionic and dichorionic twins separately. We next used data collected between Jan 1st 2018 and Apr 30th 2018, encompassing 12,371 live births, to calculate the SGA and LGA ratios using birth weight references in Australia, South Korea and China (based on birth defects surveillance system) and birth weight percentiles calculated in this study. Compared to dichorionic twins, monochorionic twins had lower birth weights at 25 to 42 weeks of gestation. The calculated SGA and LGA ratios were relatively stable compared to the other references.